Regulation of body weight and energy homeostasis by neuronal cell adhesion molecule 1 - Rathjen, Thomas; Yan, Xin; Kononenko, Natalia L; Ku, Min-Chi; Song, Kun; Ferrarese, Leiron; Tarallo, Valentina; Puchkov, Dmytro; Kochlamazashvili, Gaga; Brachs, Sebastian; Varela, Luis; Szigeti-Buck, Klara; et al. (Nature neuroscience, 2017)
The precise mechanisms that cause human obesity remain unknown. Here the authors illustrate how increased expression of Cadm1, a mediator of synapse assembly, is relevant to weight gain. Reduction of Cadm1 in multiple brain regions promoted weight loss, and these observations provide insight into the neuronal pathways contributing to obesity. Susceptibility to obesity is linked to genes regulating neurotransmission, pancreatic beta-cell function and energy homeostasis. Genome-wide association studies have identified associations between body mass index and two loci near cell adhesion molecule 1 ( CADM1 ) and cell adhesion molecule 2 ( CADM2 ), which encode membrane proteins that mediate synaptic assembly. We found that these respective risk variants associate with increased CADM1 and CADM2 expression in the hypothalamus of human subjects. Expression of both genes was elevated in obese mice, and induction of Cadm1 in excitatory neurons facilitated weight gain while exacerbating energy expenditure. Loss of Cadm1 protected mice from obesity, and tract-tracing analysis revealed Cadm1-positive innervation of POMC neurons via afferent projections originating from beyond the arcuate nucleus. Reducing Cadm1 expression in the hypothalamus and hippocampus promoted a negative energy balance and weight loss. These data identify essential roles for Cadm1-mediated neuronal input in weight regulation and provide insight into the central pathways contributing to human obesity.